Impact of Interest Rates Changes on Banking Profitability Sector in India: An Empirical Research on the Profitability Performance of Selected Nationalized Banks in India - Hingu Hitenkumar Dineshbhai (Journal of Social Commerce, 2022)
The study designed the impact of an interest rate change on the profitability of the banking sector in India. In this work comparative analysis of various profitability performance ratios like ROA, ROE, ROCE, Net Profit Margin Ratio, EPS, etc… and also find out the impact of interest rate on banks profitability with the help of correlation and regression analysis of selected nine nationalized banks in India. The data is collected through various annual reports of selected respective banks from 2011-12 to 2019-20. For the analysis, the data researchers have used various statistical tools like Mean, Ratio, Correlation Analysis, and Regression Analysis. This study concluded that out of all selected ratios, ROA, ROCE, Net Profit Margin Ratio, Net Interest Income/Total assets, Net Interest Margin Ratio and Capital adequacy Ratio indicated that null hypothesis is rejected which means there is a significant difference between these ratios of selected nationalized banks during the study period and also found that Bank Rate has significantly impacted on Net Profit Margin Ratio in all selected nationalized banks in India.